5-minute selling the proven, simple system that can double your sales...even when you don't have time - Goldfayn, Alex (Gildan Audio, 2020)
5-Minute Selling presents a proven, simple process that can double your sales, even if you don't have time for an elaborate new sales system. When you spend your days scrambling to take orders and resolving customer issues, there is little time for new sales techniques. This book is for you. In 5-Minute Selling, Alex Goldfayn describes how thousands of his clients and workshop attendees have generated dramatic annual sales growth with short bursts of action throughout the day. With three-second efforts throughout the day, you can add 50 to 100% to your sales.The techniques in this book are simple but powerful: You'll learn the power of picking up the phone proactively to call customers and prospects when nothing is wrong, because almost nobody does this. You'll get approaches for offering customers additional products and services-and asking about what else they are buying elsewhere-because almost nobody does this either.You'll also learn about the low-tech but incredibly effective singular impact of the hand-written note In short, 5-Minute Selling is about showing customers and prospects that we care about them more than our competition does with simple, repeated, lightning-fast, high-value, consistent communications.